I believe it would be $4,399.15 because if you use the formula I=P*R*T
P=62,845
R=0.07 or 7%
T=1 year period
So overall your equation is 62845*0.07*1=$4,399.15
Now at this point the interest is added onto the principal amount to figure out some new amount after one year so:
62845.00+4399.15=$67,244.15
X²+15x+36<0
at first solve quadratic equation
D=b²-4ac= 225-4*1*36= 81
x=(-b+/-√D)/2a
x=(-15+/-√81)/2= (-15+/-9)/2
x1=(-15-9)/2=-12
x2=(-15+9)/2=-3
we can write x²+15x+36<0 as (x+12)(x+3)<0
(x+12)(x+3)<0 can be 2 cases, because for product to be negative one factor should be negative , and second factor should be positive
1 case) x+12<0, and x+3>0,
x<-12, and x>-3
(-∞, -12) and(-3,∞) gives empty set
or second case) x+12>0 and x+3<0
x>-12 and x<-3
(-12,∞) and (-∞,-3) they are crossing , so (-12, -3) is a solution of this inequality
Answer:
The answer is 1.2
Step-by-step explanation:
Answer:
To multiply two numbers in scientific notation, multiply their coefficients and add their exponents. To divide two numbers in scientific notation, divide their coefficients and subtract their exponents. In either case, the answer must be converted to scientific notation.
Step-by-step explanation:
Have A Blessed Day :)